The Development of River-based Intermodal Transport: The Case of Ukraine - K. Grushevska; T. Notteboom (Journal of International Logistics and Trade, 2016)
It should be noted that the (inland waterway transport) IWT in Ukraine currently is in its infancy in comparison with other land based transport means (rail and road) and with other countries that possess navigable rivers. This paper is an extension of the research initiated by Grushevska and Notteboom (2015) where the concepts of intermediacy and centrality were introduced in order to assess the role of Ukraine in the global and regional transport networks. The list of key obstacles for Ukraine’s intermediacy function included IWT related barriers such as: (i) deficient inland waterway infrastructure, (ii) high IWT costs (fees for bridges, locks etc.) and (iii) pilotage charges. To date the transportation to/from ports is mainly fulfilled by road or by rail based multimodal transport solutions. We present the unutilized potential of Ukrainian IWT that needs to be efficiently exploited for the benefit of the national economy and national transport system. This study intends to enrich the limited academic research on IWT systems in a transition stage, as exemplified by the case of Ukraine.